Measuring alcohol consumption in population surveys: a review of international guidelines and comparison with surveys in England - Nugawela, Manjula D.; Langley, Tessa; Szatkowski, Lisa; Lewis, Sarah (Oxford University Press, 2016)
Aims: To review the international guidelines and recommendations on survey instruments for measurement of alcohol consumption in population surveys, and to examine how national surveys in England meet the core recommendations. Methods: A systematic search for international guidelines for measuring alcohol consumption in population surveys was undertaken. The common core recommendations for alcohol consumption measures and survey instruments were identified. Alcohol consumption questions in national surveys in England were compared with these recommendations for specific years and over time since 2000. Results: Four sets of international guidelines and three core alcohol consumption measures (alcohol consumption status, average volume of consumption, frequency and volume of binge drinking) with another optional measure (drinking context) were identified. English national surveys have been inconsistent over time in including questions that provide information on average volume of consumption but have not included questions on another essential alcohol consumption measure, frequency of heavy episodic drinking. Instead they have used questions that focus only on maximum volume of alcohol consumed on any day in the previous week. Conclusions: International guidelines provide consistent recommendations for measuring alcohol consumption in population surveys. These recommendations have not been consistently applied in English national surveys and this has contributed to the inadequacy of survey measurements for monitoring vital aspects of alcohol consumption in England over recent years.